Severe diffuse multivessel coronary calcification in first-degree relatives: A case series - Suryo Baskoro, Shalahuddin; Ramadhiani, Risa; Filano, Marco; Saifur Rohman, Muhammad (Universitas Brawijaya, 2026)
Background: Coronary artery disease (CAD) in first degree relatives may represent a clinical pattern associated with diffuse calcification, extensive vessel involvement, and increased procedural complexity. Such cases often present with severe multivessel disease that may require advanced revascularization strategies. Case Presentations: Three related patients aged 66–71 years, consisting of three first-degree relatives, presented with progressive angina despite optimal medical therapy. Hypertension was present in all, dyslipidemia in two, and one male had heart failure with mildly reduced ejection fraction (41%). None had diabetes, chronic kidney disease, or a smoking history. Coronary angiography revealed diffuse, heavily calcified three-vessel disease in two patients and two vessel disease in one patient. The first case (71F) underwent drug-eluting stent (DES) implantation in the left anterior descending (LAD) artery; right coronary artery (RCA) lesion preparation/atherectomy was attempted but definitive RCA stenting was not performed, and the RCA was managed conservatively. The second case (66M) had chronic total occlusions of the RCA and LCx, with rotablator-assisted DES implantation performed on the target lesion. The third case (68F) had a critical OM1 lesion treated with DES; a moderate LAD lesion was assessed with diastolic hyperemia-free ratio (DFR) and confirmed ischemia prior to staged LAD DES implantation. All procedures were completed without periprocedural complications. Conclusions: These related cases demonstrated a recurring angiographic pattern of diffuse, calcified multivessel CAD, suggesting complex interplay between metabolic risk factor and potential hereditary component.